Validation of standardized questionnaires evaluating symptoms of depression in rheumatoid arthritis patients - approaches to screening for a frequent and yet underrated challenge - Englbrecht, Matthias; Alten, Rieke; Aringer, Martin; Baerwald, Christoph G.; Burkhardt, Harald; Eby, Nancy; Fliedner, Gerhard; Gauger, Bettina; Henkemeier, Ulf; Hofmann, Michael W.; Kleinert, Stefan; Kneitz, Christian; et al. (Arthritis & Rheumatism-Arthritis Care & Research, 2016)
To validate standard self-reporting questionnaires for depression screening in patients with rheumatoid arthritis (RA) and compare these measures to each other and to the Montgomery-Åsberg Depression Rating Scale (MADRS), a standardized structured interview.In 9 clinical centers across Germany, depressive symptomatology was assessed in 262 adult RA patients at baseline (T0) and at 12 ± 2 weeks follow-up (T1) using the WHO Five Well-Being Index (WHO-5), the Patient Health Questionnaire-9 (PHQ-9), and the Beck Depression Inventory (BDI-II). Construct validity of these depression questionnaires (using convergent and discriminant validity) was evaluated using Spearman correlations at both time points. The test-retest reliability of the questionnaires was evaluated in RA patients who had not undergone psychotherapeutic intervention or received antidepressants between T0 and T1. The sensitivity and the specificity of the questionnaires were calculated using the results of the MADRS, a structured interview, as gold standard.According to the Spearman correlation coefficients all questionnaires met convergent validity criteria (? > |0.50|) with the BDI-II performing best while correlations with age and disease activity for all questionnaires met the criteria for discriminant validity (? < |0.50|). The only questionnaire to meet the predefined retest reliability criterion (? >= 0.70) was the BDI-II (rs = 0.77) which also achieved the best results for both sensitivity and specificity >80% when using the MADRS as the gold standard.The BDI-II best met the predefined criteria and the PHQ-9 met most validity criteria with lower sensitivity and specificity. This article is protected by copyright. All rights reserved.
EVALuna:32493